Validation of Chronic Inflammatory Demyelinating Polyradiculoneuropathy Coding in US Claims Data - Okonkwo, Joshua U.; Williams, Erika K.; Sadjadi, Reza; Schneeweiss, Sebastian; Anderson‐Smits, Colin; Ay, Hakan; Spalding, William; Anand, Priyanka; Lu, Zhigang; Lin, Kueiyu Joshua (Pharmacoepidemiology and drug safety, 2025)
ABSTRACT Purpose Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a rare autoimmune condition of the peripheral nervous system. The validity of the CIDP diagnosis code in claims data is unclear. Methods We conducted a validation study testing the performance of claims‐based algorithms in identifying CIDP cases, using electronic health record data from the Mass General Brigham Integrated Health Care System linked with Medicare claims data from 01/01/2008 to 12/31/2020. The algorithms require a record of intravenous immunoglobulin (IVIG) use and International Classification of Diseases 9th/10th Revision (ICD9/10) CIDP codes before (including) the date of IVIG use. The positive predictive values (PPVs) of each claims‐based algorithm were calculated against the reference standard for CIDP and chronic immune‐mediated acquired neuropathy established through chart review by two board‐certified neurologists using a standardized ion tool. Results The study cohort consisted of 140 patients (59 in the ICD9 and 81 in the ICD10 era). The PPV of the algorithm requiring at least one CIDP diagnosis code before IVIG use was 66.2% (95% confidence interval [CI], 58.0–74.3). The PPV improved to 71.2% (62.7–79.6) when requiring at least two CIDP codes before IVIG use. The PPV for patients with at least one CIDP code who met the European Academy of Neurology/Peripheral Nerve Society 2021 diagnostic criteria was 30.0% (22.1–37.9). Conclusion We found that a patient cohort identified using claims‐based CIDP diagnoses included a substantial number of patients with other chronic inflammatory acquired neuropathies not formally recognized as CIDP by clinical consensus criteria. Requiring two CIDP codes can improve PPVs.